Sincronía y diacronía de los sonidos retroflejos del quechua huanca desde la fonética articulatoria - Ibarra Valer, Richard Anthony (2019)
Quechua is a language widely studied by linguists. It has been classified, mainly, in different varieties according to its phonemic and morphemic characteristics. In this way, Quechua huanca or wanka is a variety that presents, among other characteristics, retroflex sounds: one affricate and another fricative. Consequently, these sounds, or only the affricate according to other authors, are within the phonological inventory of the so-called protoquechua, since they are complex sounds due to their articulation. The objective of this article is to provide a state of the art on retro-reflective sounds in Quechua Wanka and to evaluate the articulatory characteristics of these types of sounds inside of other Andean languages as Cauqui and Jaqaru in light of new advances in phonetic analysis, especially, since the contribution of Hamman (2003) on the point of lingual articulation.